The Berlin-Strasbourg Apocryphon: a Coptic apostolic memoir - Suciu, Alin (Wissenschaftliche Untersuchungen zum Neuen Testament, 2017)
History of research on the Berlin-Strasbourg Apocryphon -- The manuscripts -- The content of the Berlin-Strasbourg Apocryphon and the relationship between the manuscripts -- The place of the Berlin-Strasbourg Apocryphon in coptic literature -- Text and translation